An overview of studies on financial resilience among women led SMES after Covid-19 pandemic: a systematic literature review and bibliometric analysis - Mahadi, Nur Farhah; Yusuf, Muhammad-Bashir; Kassim, Salina; Abd Samad, Khairunnisa (Society of Research Administrators International, 2023)
Small-business owners faced a variety of difficulties during the pandemic, including interruptions to operations, issues with supply chains, a lack of internal capital to cover ongoing operating costs, increased insolvency risks, and a lack of sufficient government support during the protracted lockdowns and severe movement restrictions. This paper provides a thorough summary of research on the financial resilience of small and medium-sized businesses (SMEs) run by women. In addition to determining how the field of financial resilience of women-led Small and Medium Enterprises (SMEs) research during and after pandemics is changing over time, the study aims to identify which approaches or models are most commonly used in relation to SMEs' financial resilience. We searched scholarly publications for relevant papers and found them using the Scopus and Web of Science databases. Between 2020 and 2023, a total of 180 publications were released. For the bibliometric analysis, the R-based Biliometrix library was used. Our findings show that different theories and approaches are employed to explain the financial resilience of small and medium-sized businesses (SMEs) owned and operated by women. Furthermore, the study employed the Descriptive research model consistently, with the United States and Asia setting the bar for model and technique adoption. The bibliometric study indicates that there is a sharp increase in scholarly interest in the financial resilience of Small and Medium Enterprises (SMEs) run by women. Global scientists have shown a strong desire to collaborate and learn more about this challenging subject. This research is supported by the Ministry of Education (MOE) through Fundamental Research Grant Scheme (FRGS/1/2021/SS01/UIAM/03/3).